Potential of distributed wood-based biopower systems serving basic electricity needs in rural Uganda - Da Silva, Izael (Elsevier B.V ScienceDirect, 2015)
Current efforts to improve electricity services in Uganda evolve around satisfying growing urban demand as well as stabilizing and boosting a low electricity supply. Although virtually non-existent, rural electrification is receiving very little attention. This paper investigates the potential of wood-based biopower fueled from coppicing shrubs on its feasibility to provide affordable basic electricity services to rural Ugandan households. Gasification was the specific technology we assessed. In the calculations, a worst case scenario was chosen for wood-based biopower to compete with alternative sources of electricity: Cost and land use estimates assumed a rather high household consumption (30 kWh/month), a low household size (8 persons), a low area productivity (3 oven-dried tons per ha per year), a low electrical conversion efficiency (15%) and a high demand competing for fertile land with the biopower system. Cost estimates considered a high biomass price (18.5 US$/odt), a low capacity factor for the biopower system of 0.5 (therefore requiring installation of a larger unit) and high capital costs of 2300 US$ per kW installed. Additional pressure on fertile land would be negligible. Such biopower systems can outcompete other sources of electricity from a micro and macro-economic standpoint when looking at the local scale. Results indicate that biopower can deliver better and more energy services at 47 US$/yr and household or 0.11 US$/kWh which is below current average costs for e.g. off-grid lighting in rural Ugandan households. Additionally, only this biopower option offers the ability to households, sell wood to the biopower system and contribute at least four times as much to the local economy than the other electricity options used as terms of comparison. Further research has to focus on developing business plans and loan schemes for such biopower options including sustainable fuelwood supply chains based on coppicing shrubs which have the ability to contribute to agricultural site improvements. The approach outlined in this paper can further serve as a general framework to compare different options of electricity production across technologies and fuel sources especially for rural development purposes incorporating a multitude of aspects.
Keywords: Rural electrification; Gasification; Distributed electricity; Fuelwood; Electricity costs